1938
DOI: 10.3733/hilg.v11n10p559
|View full text |Cite
|
Sign up to set email alerts
|

The effect of riboflavin and the filtrate factor on egg production and hatchability

Abstract: Lepkovsky, et at: Riboflavin and the Filtrate Factor 561 polished rice, and soybean oil used in these rations were products of commerce. The extracted sardine meal was a special product extracted with a hydrocarbon solvent. The special salt was sodium chloride plus 0.010 per cent iron as ferrous sulfate and 0.001 per cent copper as copper sulfate. These rations were supplemented as detailed in table 2. Preparation of S•upplements.-The 1935-36 r'iboflavin fuller's-earth adsorbate was prepared by shaking "They w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

1939
1939
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…This is in agreement with the results as reported by Davis, Norris, and Heuser (1938b) and Lepkovsky et al (1938). Two weeks after beginning supplementary feeding of riboflavin the hatchability of fertile eggs had been increased to approximately 80 percent.…”
supporting
confidence: 94%
“…This is in agreement with the results as reported by Davis, Norris, and Heuser (1938b) and Lepkovsky et al (1938). Two weeks after beginning supplementary feeding of riboflavin the hatchability of fertile eggs had been increased to approximately 80 percent.…”
supporting
confidence: 94%
“…S INCE 1936, experiments designed to improve the hatchability obtained with a diet consisting primarily of polished rice and sardine fishmeal (Lepkovsky, Taylor, Jukes and Almquist, 1938) have been in progress. Until the experiments reported in this paper, satisfactory hatchability had never been secured, although through numerous tests, conducted with the cooperation of Dr. S. Lepkovsky and Dr. H. J. Almquist, the original ration had been improved by the addition of various supplements to sustain essentially normal rates of egg production (unpublished data).…”
Section: University Of California Berkeleymentioning
confidence: 99%
“…Bethke et al (1937) identified riboflavin as the substance in the vitamin G complex responsible for the enhancement of hatchability of chicks. Lepkovsky et al (1938) showed the relationship between laying hen diet, egg riboflavin concentrations, and various embryonic deficiency signs by measuring albumen riboflavin concentrations by a photometric assay. Hunt et al (1939) showed that the riboflavin requirement for maximum hatchability was higher than that for egg production.…”
Section: Introductionmentioning
confidence: 99%